Fabrication of 316L stainless steel (SS316L) foam via powder compaction method - Abdullah, Zulaikha (2015)
Metal foam is the cellular structures that made from metal and have pores in their structures. Metal foam also known as the porous metals, which express that the structure has a large volume of porosities with the value of up to 0.98 or 0.99. Porous 316L stainless steel was fabricated by powder metallurgy route with the composition of the SS316L metal powder as metallic material, polyethylene glycol (PEG) and Carbamide as the space holder with the composition of 95, 90, 85, 80, and 75 of weight percent (wt. %). The powders were mixed in a ball mill at 60 rpm for 10 minutes and the mixtures were put into the mold for the pressing. The samples were uniaxially pressed at 3 tons and heat treated by using box furnace at different sintering temperature which are 870°C, 920°C, and 970°C separately. The suitable sintering temperature was obtained from the Thermal Gravimetric Analysis (TGA). There are several tests that have been conducted in order to characterize the physical properties of metal foam such as density and porosity testing, and the morphological testing (Scanning Electron Microscopy (SEM)), and Energy Dispersive X-ray (EDX). From the result, it can be conclude that, the sintering temperature of 920°C was compatible temperature in order to produce the metal foams which have large pores. Other than that, the composition of 85 and 75 wt. % is the best compositions in order to creates the homogenous mixture and allow the formation of large pore uniformly compared to other compositions which in line with the objective to produce foams with low density and high porosity which suitable for implant applications. The average pore size was within range 38.555μm to 54.498 μm which can be classified as micro pores.